Parathyroid gland angiography with indocyanine green fluorescence to predict parathyroid function after thyroid surgery. Issue 5 (11th February 2016) - Vidal Fortuny, J; Belfontali, V; Sadowski, S M; Karenovics, W; Guigard, S; Triponez, F
Abstract: Background: Postoperative hypoparathyroidism remains the most common complication following thyroidectomy. The aim of this pilot study was to evaluate the use of intraoperative parathyroid gland angiography in predicting normal parathyroid gland function after thyroid surgery. Methods: Angiography with the fluorescent dye indocyanine green (ICG) was performed in patients undergoing total thyroidectomy, to visualize vascularization of identified parathyroid glands. Results: Some 36 patients underwent ICG angiography during thyroidectomy. All patients received standard calcium and vitamin D supplementation. At least one well vascularized parathyroid gland was demonstrated by ICG angiography in 30 patients. All 30 patients had parathyroid hormone (PTH) levels in the normal range on postoperative day (POD) 1 and 10, and only one patient exhibited asymptomatic hypocalcaemia on POD 1. Mean(s.d.) PTH and calcium levels in these patients were 3·3(1·4) pmol/l and 2·27(0·10) mmol/l respectively on POD 1, and 4·0(1.6) pmol/l and 2·32(0·08) mmol/l on POD 10. Two of the six patients in whom no well vascularized parathyroid gland could be demonstrated developed transient hypoparathyroidism. None of the 36 patients presented symptomatic hypocalcaemia, and none received treatment for hypoparathyroidism. Conclusion: PTH levels on POD 1 were normal in all patients who had at least one well vascularized parathyroid gland demonstrated during surgery by ICG angiography, and none required treatment for hypoparathyroidism. Abstract : New method to avoid postoperative hypoparathyroidism